2014
DOI: 10.1016/j.ymgmr.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Residual OCTN2 transporter activity, carnitine levels and symptoms correlate in patients with primary carnitine deficiency

Abstract: BackgroundThe prevalence of primary carnitine deficiency (PCD) in the Faroe Islands is the highest reported in the world (1:300). Serious symptoms related to PCD, e.g. sudden death, have previously only been associated to the c.95A > G/c.95A > G genotype in the Faroe Islands. We report and characterize novel mutations associated with PCD in the Faroese population and report and compare free carnitine levels and OCTN2 transport activities measured in fibroblasts from PCD patients with different genotypes.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…In addition to the prevalent p.N32S mutation, there is what we initially named the risk haplotype (RH); today we know that the haplotype segregates with a c.-149C>A mutation that likely affects transcription (100/336 mutant alleles) ( Analysis of carnitine transport indicated that fibroblasts from individuals homozygous for the c.95A>G (p.N32S) retained about 4% of normal transport activity (consistent with the expression studies in CHO cells reported above), compared to 18% for fibroblasts compound heterozygous for c.95A>G (p.N32S) and the risk haplotype and 29% for homozygotes for the risk haplotype [37].…”
Section: Molecular Bases Of Primary Carnitine Deficiency In the Faroesupporting
confidence: 59%
See 1 more Smart Citation
“…In addition to the prevalent p.N32S mutation, there is what we initially named the risk haplotype (RH); today we know that the haplotype segregates with a c.-149C>A mutation that likely affects transcription (100/336 mutant alleles) ( Analysis of carnitine transport indicated that fibroblasts from individuals homozygous for the c.95A>G (p.N32S) retained about 4% of normal transport activity (consistent with the expression studies in CHO cells reported above), compared to 18% for fibroblasts compound heterozygous for c.95A>G (p.N32S) and the risk haplotype and 29% for homozygotes for the risk haplotype [37].…”
Section: Molecular Bases Of Primary Carnitine Deficiency In the Faroesupporting
confidence: 59%
“…Primary carnitine deficiency in the Faroe Islands is due to specific mutations in the SLC22A5 gene encoding the OCTN2 carnitine transporter [37]. The predominant mutation is c.95A>G (p.N32S) which is found on 211 of the 336 alleles of the 168 PCD-cases.…”
Section: Molecular Bases Of Primary Carnitine Deficiency In the Faroementioning
confidence: 99%
“…She had a normal acylcarnitine profile (including C6, C8, and C10:1), and the urinary excretion of organic acids was normal, thereby excluding secondary depletion of carnitine. None of the frequent Faroese SLC22A5 mutations known to segregate in the Danish population (c.95A>G, c.825-52G>A) nor the risk haplotype (Rasmussen et al 2014) was identified. In parallel with the analyses in the infant, the mother (aged 36 years) was evaluated and turned out to have a normal free carnitine in plasma (30 mmol/L, ref.…”
Section: Case Reportmentioning
confidence: 91%
“…Founder mutations have been reported in specific geographic areas, such as p.W132X and p.S467C in Japan [83], p.R254X in the Chinese population [136], and p.N32S in the Faroe Islands [88]. In the Faroe Islands, patients with primary carnitine deficiency are either homozygous or compound heterozygous for four different mutations (c.95A>G, p.N32S; c.136C>T, p.P46S; c.131C>T, p.A44V; c.825-52G>A) and a risk-haplotype, with p.N32S being the most prevalent [142]. Patients homozygous for p.N32S had lower mean plasma carnitine levels, the lowest mean residual OCTN2 carnitine transport activity in their fibroblasts, and had a high risk of having symptoms (hypoglycemia or cardiomyopathy in children, sudden death or fatigue in adults) [142], with plasma and tissue carnitine levels dropping rapidly after discontinuation of oral carnitine supplements [143].…”
Section: Disorders Of Fatty Acid Oxidationmentioning
confidence: 99%